Deflagrations in hybrid CONe white dwarfs: a route to explain the faint Type Iax supernova 2008ha - Kromer, Markus; Ohlmann, S. T.; Pakmor, R.; Ruiter, A. J.; Hillebrandt, W.; Marquardt, K. S.; Röpke, Friedrich; Seitenzahl, I. R.; Sim, S. A.; Taubenberger, S. (Monthly notices of the Royal Astronomical Society, 2015)
Stellar evolution models predict the existence of hybrid white dwarfs (WDs) with a carbon–oxygen core surrounded by an oxygen–neon mantle. Being born with masses ∼1.1 M⊙, hybrid WDs in a binary system may easily approach the Chandrasekhar mass (MCh) by accretion and give rise to a thermonuclear explosion. Here, we investigate an off-centre deflagration in a near-MCh hybrid WD under the assumption that nuclear burning only occurs in carbon-rich material.
Gesehen am 29.05.2020